Soy 11S Globulin Acid Subunits as the Novel Food Polymer Carrier - Lei Chen; Dahai Liu; Guohua Wu; Yuanyuan Ma (International Journal of Polymer Science)
Aflatoxins were conjugated with soy 11S globulins acid subunits and the hapten-specific monoclonal antibodies (McAbs) cross-reactive with four major aflatoxins were achieved using indirect competitive ELISA screening procedure. The two antibodies (clones 1B2 and 2D3) had similar reaction efficiency with aflatoxins B1, B2, and G1 but showed a weak cross-reaction to G2. The clone 4C5 exhibited the highest sensitivity for all four aflatoxins. The concentrations of aflatoxins B1, B2, G1, and G2 at 50% inhibition for 4C5 were 1.1, 1.2, 2.1, and 17.6 pg mL−1. The results indicated that soy 11S globulin acid subunits were suitable novel carriers for aflatoxin antigen in immunization experiments and clone 4C5 could be used for simultaneous analysis of total aflatoxins.